2019
DOI: 10.12669/pjms.35.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Single versus double burr-hole drainage for chronic subdural hematoma: A study of relevant prognostic factors conducted in Pakistan

Abstract: Objective: To compare the efficacy of single versus double burr-hole for drainage of chronic subdural hematoma, keeping in consideration pertinent demographic, pre and postoperative associations. Methods: A prospective cohort study carried out in Combined Military Hospital, Multan, (December 2016-August 2018), on adults with diagnosed chronic subdural hematoma (CSDH); being segregated by randomized control trial, non-probability purposive sampling into Group-A and Group-B (who underwent single and double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…4 A prospective cohort study comparing single versus double burr hole surgeries also showed that there was no difference in outcome (p=0.54). 5 A meta-analysis including 12 studies, of which 3 were RCTs, showed that there were no significant difference in recurrence rate (odds ratio [OR], 1.28; 95% confidence interval [CI], 0.92-1.78; P =0.07), complication rate (OR, 0.74; 95% CI, 0.20-2.76; P = 0.11) and morbidity (OR, 1.38; 95% CI, 0.55-3.46; P = 0.58) between single burr hole and double burr hole in the treatment of cSDH. 6 Based on this literature, a single burr hole seems not to be inferior to double burr holes in terms of recurrence in managing cSDH.…”
Section: Preferred Surgical Methodsmentioning
confidence: 99%
“…4 A prospective cohort study comparing single versus double burr hole surgeries also showed that there was no difference in outcome (p=0.54). 5 A meta-analysis including 12 studies, of which 3 were RCTs, showed that there were no significant difference in recurrence rate (odds ratio [OR], 1.28; 95% confidence interval [CI], 0.92-1.78; P =0.07), complication rate (OR, 0.74; 95% CI, 0.20-2.76; P = 0.11) and morbidity (OR, 1.38; 95% CI, 0.55-3.46; P = 0.58) between single burr hole and double burr hole in the treatment of cSDH. 6 Based on this literature, a single burr hole seems not to be inferior to double burr holes in terms of recurrence in managing cSDH.…”
Section: Preferred Surgical Methodsmentioning
confidence: 99%
“…Surgery is currently the common clinical treatment for CSDH, including single hole drainage, double borehole drainage and minimally invasive puncture drainage, but clinical practice shows that borehole drainage will cause severe trauma, which is difficult to meet the increasing needs of patients. 5,6 In recent years, the application of neuroendoscopy in the treatment of CSDH has been increasingly reported. Through neuroendoscopy, the entire hematoma cavity can be visualized to completely remove hematoma and trabecular-like structure and adequately stop bleeding, and a hematoma cavity drain tube can be placed under direct visualization.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is currently the common clinical treatment for CSDH, including single hole drainage, double borehole drainage and minimally invasive puncture drainage, but clinical practice shows that borehole drainage will cause severe trauma, which is difficult to meet the increasing needs of patients. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic subdural hematoma (CSDH) is a common and frequently occurring disease, and the incidence rises with age (Sahyouni et al, 2017). Burr-hole drainage is a routine operation for the treatment of CSDH (Tang et al, 2018;Soleman et al, 2019;Khan et al, 2019), but the recurrence rate is ∼10-39% (Kim et al, 2014;Jang et al, 2015). Local inflammatory responses may contribute to the recurrence of CSDH (Jaiswal and Sontakke, 2012;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%